Automatic drain cleaner / Nur Daliela Wahida Zamry - Khairuanuar, Nur Dayana Asilah (2022)
In this research study, a mechanical drain cleaner is offered as a replacement for human drainage cleaning. Cleaning drain using the usual tool like drain hoe and rubbish pickers is not an effective way and can picked rubbish in a small amount.Futhermore, people or labours also easy to catch infections due to the large amount of waste in drain. Therefore, the objective of this product is to design a product that can pick up rubbish from the drain using SolidWorks software and to fabricate an automatic drain cleaner. In this product system consists of metal teeth jaws that wait at the bottom of the mechanism.After a particular time intervals the jaw lifts up using a motorized shaft which is connected using a chain to the jaws. The jaws then reach at the top and the waste will dump into the basket.In conclusion, this automatic drain cleaner is way more effective than the usual one and can prevent the high risk of infections.